Calcium supplementation amongst postmenopausal women: effect on serum calcium, phosphorus and magnesium level - Mohd Fadzwi, Fazlini; Abdul Rahman, Suriah; Yassin, Zaitun; Kandiah, Mirnalini; Chee, Winnie Siew Swee; Chan, Yoke Mun; Chan, Siew Pheng (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
This study assessed the effect of calcium supplementation towards the change in serum calcium, phosphorus and magnesium level. We carried out a randomized controlled trial of calcium supplementation in 113 postmenopausal women for 24 months period study. Subjects were randomly assigned into two groups. Subjects in Calcium Supplemented Group (CSG) were to take calcium supplement (1200 mg/day) while the Control Group were not given any placebo and advised to continue with their regular diet. The study showed that calcium supplementation helps to increased daily intake of calcium amongst the subject which in results helping to maintain the serum calcium level within normal range. The serum magnesium and phosphorus level in this study were kept at a normal range although there is a slight decrease in serum phosphorus levels may be due to a reduction in the daily intake of the mineral.